Searching for Best Predictors of Paralinguistic Comprehension and Production of Emotions in Communication in Adults With Moderate Intellectual Disability - Calić, Gordana; Glumbić, Nenad; Petrović-Lazić, Mirjana; Đorđević, Mirjana; Mentus, Tatjana (Frontiers in Psychology, 2022)
Paralinguistic comprehension and production of emotions in communication include the skills of recognizing and interpreting emotional states with the help of facial expressions, prosody and intonation. In the relevant scientific literature, the skills of paralinguistic comprehension and production of emotions in communication are related primarily to receptive language abilities, although some authors found also their correlations with intellectual abilities and acoustic features of the voice. Therefore,the aim of this study was to investigate which of the mentioned variables(receptive language ability, acoustic features of voice, intellectual ability, social-demographic),presents the most relevant predictor of paralinguistic comprehension and paralinguistic production of emotions in communication in adults with moderate intellectual disabilities(MID). The sample included 41 adults with MID, 20-49 years of age(M = 34.34, SD = 7.809), 29 of whom had MID of unknown etiology, while 12 had Down syndrome. All participants are native speakers of Serbian. Two subscales from The Assessment Battery for Communication – Paralinguistic comprehension of emotions in communication and Paralinguistic production of emotions in communication, were used to assess the examinees from the aspect of paralinguistic comprehension and production skills. For the graduation of examinees from the aspect of assumed predictor variables, the following instruments were used: Peabody Picture Vocabulary Test was used to assess receptive language abilities, Computerized Speech Lab(“Kay Elemetrics” Corp., model 4300)was used to assess acoustic features of voice, and Raven’s Progressive Matrices were used to assess intellectual ability. Hierarchical regression analysis was applied to investigate to which extent the proposed variables present an actual predictor variables for paralinguistic comprehension and production of emotions in communication as dependent variables. The results of this analysis showed that only receptive language skills had statistically significant predictive value for paralinguistic comprehension of emotions(β = .468, t = 2.236, p < .05), while the factor related to voice frequency and interruptions, form the domain of acoustic voice characteristics, displays predictive value for paralinguistic production of emotions(β = .280, t = 2.076, p < .05). Consequently, this study, in the adult population with MID, evidenced a greater importance of voice and language in relation to intellectual abilities in understanding and producing emotions.